WISH YOU WERE HERE - Fuhrman, Isabelle, 1997-; Massoud, Mena; Fails, Jimmie (Lionsgate, 2026)
When the perfect night with a perfect stranger ends suddenly the next morning, Charlotte searches for answers and meaning in her disappointing life until she uncovers a secret that changes everything.